ECONOMETRIC MODELING OF THE LEVEL OF OFF-THE-BOOKS ECONOMY ON THE SOCIO-ECONOMIC PERFORMANCE HAS KAZAKHSTAN - Toty K. Bekzhanova (Статистика и экономика, 2016)
This article discusses the application of mathematical and statistical methods to the study non-observed economy of Kazakhstan. According to the results obtained by using correlation, regression and component analysis, the factors affecting the proportion of non-observed economy are studied.